Polymethacrylate coated electrospun PHB fibers: An exquisite outlook for fabrication of paper-based biosensors - Hosseini, S.; Azari, P.; Farahmand, E.; Gan, S.N.; Rothan, H.A.; Yusof, R.; Koole, L.H.; Djordjevic, I.; Ibrahim, F. (Elsevier, 2015)
Electrospun polyhydroxybutyrate (PHB) fibers were dip-coated by polymethyl methacrylate-co-methacrylic acid, poly(MMA-co-MAA), which was synthesized in different molar ratios of the monomers via free-radical polymerization. Fabricated platfrom was employed for immobilization of the dengue antibody and subsequent detection of dengue enveloped virus in enzyme-linked immunosorbent assay (ELISA). There is a major advantage for combination of electrospun fibers and copolymers. Fiber structre of electrospun PHB provides large specific surface area available for biomolecular interaction. In addition, polymer coated parts of the platform inherited the premanent presence of surface carboxyl (-COOH) groups from MAA segments of the copolymer which can be effectively used for covalent and physical protein immobilization. By tuning the concentration of MAA monomers in polymerization reaction the concentration of surface -COOH groups can be carefully controlled. Therefore two different techniques have been used for immobilization of the dengue antibody aimed for dengue detection: physical attachment of dengue antibodies to the surface and covalent immobilization of antibodies through carbodiimide chemistry. In that perspective, several different characterization techniques were employed to investigate the new polymeric fiber platform such as scanning electron microscopy (SEM), atomic force microscopy (AFM), water contact angle (WCA) measurement and UV-vis titration. Regardless of the immobilization techniques, substantially higher signal intensity was recorded from developed platform in comparison to the conventional ELISA assay. (C) 2015 Elsevier B.V. All rights reserved.